ANALISIS DETERMINAN PERSISTENSI LABA - Marhamah Marhamah; Edy Susanto; Vita Nida Sari (JURNAL STIE SEMARANG, 2020)
Earnings persistence is one component of earnings quality. Earnings persistence is a measure that explains the company's ability to maintain the current amount of profit into the future. Profits of companies that are able to survive in the future will reflect quality profits. The purpose of this study was to determine the effect of leverage, cash flow accruals, sales volatility, and size of company on earnings persistence. The population used in this study were various industrial sector manufacturing companies listed on the Indonesia Stock Exchange, with the determination of the sample using purposive sampling in order to obtain 23 companies. The results showed that the leverage variable does not have a significant effect on earnings persistence. Accruals cash flow has a significant effect on earnings persistence. Sales volatility has no significant effect on earnings persistence. Size of Company has no significant effect on earnings persistence. The coefficient of determination (Adjusted R Square) is 0.259, this means that the variable leverage, cash flow accruals, sales volatility, size of company has a role of 25.9%. With a determination coefficient of 25.9%, it is expected that the company will be able to present financial reports that reflect the quality of earnings so that it can become a reference for potential investors / investors in investing